Glecaprevir/pibrentasvir for hepatitis C virus genotype 3 patients with cirrhosis and/or prior treatment experience: A partially randomized phase 3 clinical trial. Issue 2 (4th January 2018) - Wyles, David; Poordad, Fred; Wang, Stanley; Alric, Laurent; Felizarta, Franco; Kwo, Paul Y.; Maliakkal, Benedict; Agarwal, Kosh; Hassanein, Tarek; Weilert, Frank; Lee, Samuel S.; Kort, Jens; et al.
Abstract : This study assessed the efficacy and safety of ribavirin‐free coformulated glecaprevir/pibrentasvir (G/P) in patients with hepatitis C virus genotype 3 infection with prior treatment experience and/or compensated cirrhosis, a patient population with limited treatment options. SURVEYOR‐II, Part 3 was a partially randomized, open‐label, multicenter, phase 3 study. Treatment‐experienced (prior interferon or pegylated interferon ± ribavirin or sofosbuvir plus ribavirin ± pegylated interferon therapy) patients without cirrhosis were randomized 1:1 to receive 12 or 16 weeks of G/P (300 mg/120 mg) once daily. Treatment‐naive or treatment‐experienced patients with compensated cirrhosis were treated with G/P for 12 or 16 weeks, respectively. The primary efficacy endpoint was the percentage of patients with sustained virologic response at posttreatment week 12 (SVR12). Safety was evaluated throughout the study. There were 131 patients enrolled and treated. Among treatment‐experienced patients without cirrhosis, SVR12 was achieved by 91% (20/22; 95% confidence interval [CI], 72‐97) and 95% (21/22; 95% CI, 78‐99) of patients treated with G/P for 12 or 16 weeks, respectively. Among those with cirrhosis, SVR12 was achieved by 98% (39/40; 95% CI, 87‐99) of treatment‐naive patients treated for 12 weeks and 96% (45/47; 95% CI, 86‐99) of patients with prior treatment experience treated for 16 weeks. No adverse events led to discontinuation of study drug, and no serious adverse events were related to study drug. Conclusion : Patients with hepatitis C virus genotype 3 infection with prior treatment experience and/or compensated cirrhosis achieved high SVR12 rates following 12 or 16 weeks of treatment with G/P. The regimen was well tolerated. (Hepatology 2018;67:514‐523).